2020
DOI: 10.1111/jrh.12515
|View full text |Cite
|
Sign up to set email alerts
|

Family Physician Burnout Does Not Differ With Rurality

Abstract: Burnout affects about half of family physicians (FPs). Minimal research exists which examines the impact of urban and rural practice settings on FP burnout. In this study, we examined whether rural practice is associated with FP burnout.Methods: Data from the 2017 and 2018 American Board of Family Medicine Family Medicine Certification examination registration questionnaire were used. We limited our sample to FPs in continuity care in the United States. The questionnaire is a mandatory component of registratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 17 publications
1
21
0
6
Order By: Relevance
“…In total, we included 12 studies with 38,732 participants from 6927 citations identified from literature search strategies (see Fig. 1) [20][21][22][23][24][25][26][27][28][29][30][31]. Among these included studies, eleven were cross-sectional studies [20][21][22][23][24][26][27][28][29][30][31], and one was a cohort study [25].…”
Section: Description Of Studies Selection Processmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, we included 12 studies with 38,732 participants from 6927 citations identified from literature search strategies (see Fig. 1) [20][21][22][23][24][25][26][27][28][29][30][31]. Among these included studies, eleven were cross-sectional studies [20][21][22][23][24][26][27][28][29][30][31], and one was a cohort study [25].…”
Section: Description Of Studies Selection Processmentioning
confidence: 99%
“…1) [20][21][22][23][24][25][26][27][28][29][30][31]. Among these included studies, eleven were cross-sectional studies [20][21][22][23][24][26][27][28][29][30][31], and one was a cohort study [25]. The included studies were published between 1996 [27] and 2020 [30,31] and were conducted in the USA (N = 6) [21-23, 27, 28, 31], in Canada (N = 4) [20,24,26,29], in Portugal (N = 1) [25], and in Switzerland (N = 1) [30].…”
Section: Description Of Studies Selection Processmentioning
confidence: 99%
See 3 more Smart Citations